Recognition of Petroleum Origin in the Northern Piedmont Belt of Turpan-Hami Basin and Its Significance - Bin Hao; Zhanlong Yang; Jing Zhang; Shuangwen Li; Lihua Wei; Jianglong Shi; Zaiguang Li; Jun Yao; Xiaopeng Huang; Qingpeng Wu (Geofluids)
The Turpan-Hami Basin has been considered as the most typical coal-derived-oil basin in China for a long time. However, with the deepening exploration, this theory has caused increasing controversy and some scholars doubt that Permian or Jurassic dark mudstone may be the main source rocks. The origin uncertainty even restricts deciding the exploration direction. Taking the reservoirs of the northern piedmont belt as an example, this paper analyzed oil sources by the geochemical characteristic comparison of inclusions, crude oil, and source rocks. Combined with the previous studies, the hydrocarbon accumulation model is established. The results show that the geochemical characteristics of the inclusions and oil in most areas are obviously different. Most reservoirs are mixed-source reservoirs. The oil sources varied in different regions. In the area near Bogeda, C19+20TT and C28 sterane content in oil are high, indicating that coal and Permian lacustrine mudstone are main contributors. Far away from Bogeda, bounded by the thick coal seam of Xishanyao Formation, oil sources are quite different. Above it, C19+20TT is high and gammacerane and pregnane are low, C29>>C28>C27sterane, indicating that coal and carbonaceous mudstone are main sources. Under that, C21TT and C23TT content in the inclusions are high, C29≥C27>C28sterane, while C19+20TT and pregnane content in the oil are also high, indicating that it is a mixed oil system mainly derived from Jurassic lacustrine mudstone and coal. Lacustrine mudstone has higher contribution. This phenomenon is mainly related to different fault styles in different zones. Near Bogeda, strong stress caused vertical large faults developed, which connected Jurassic reservoirs and Permian source rocks. Far from Bogeda, the faults sliped along the thick coal seam, It is difficult for deep hydrocarbon to enter the shallow layer. In the future, it should be considered to look for the traps with relatively high-quality reservoir-cap combinations for exploration in the hydrocarbon supply window of effected hydrocarbon kitchens.